Arti Penting Hukum Antartata Hukum untuk Indonesia - Yu Un Opusunggu (Badan Pembinaan Hukum Nasional, 2018)
This article discusses the importance of conflict of laws and private international law in Indonesia. Both fields of law are two-side of coin in the context of Indonesia. The author argues that many legal problems in Indonesia have their roots in the ignorance of legal pluralism. The article begins with mapping out legal pluralism since colonial period to the present. The author explains with legal pluralism calls for the science of conflict of laws/private international law. Indonesia’s attempt to attract foreign investors have entailed a series of legal reform. However, those reforms have ignored the pluralistic aspects of the legal system. The development of legal system has been caught between competing interests. The author therefore argues that understanding of the science of conflict of laws/private international law is the key for future development.